Integrasi Ekoteologi dalam Pendidikan Agama Islam - Nur Aini; Moh. Hafid Effendy (4, 2026)
The global environmental crisis has driven the Indonesian Ministry of Religious Affairs (Kementerian Agama RI) in 2025 to integrate ecotheology into the Islamic Religious Education curriculum as a response to the need for developing faith-based ecological awareness at the secondary level. This study aims to analyze the concept of ecotheology in the 2025 Ministry policy, examine strategies for integrating it into Islamic Religious Education (PAI), and identify problems and strategic solutions for Senior High Schools/Islamic Senior High Schools (SMA/MA). The method used is a descriptive-analytical literature study of policy documents, scientific articles, and relevant books. The findings show that ecotheology in the policy is built upon five Islamic principles: Tawhid, the concepts of Khalifah and Amanah, Mizan, the prohibition of israf and the encouragement of ihsan, as well as the recognition of God’s sovereignty over nature. The policy also emphasizes the concept of “social dhikr,” which interprets environmental care as an act of worship. Integration is recommended across five learning domains (Qur’an-Hadith, Creed, Ethics, Fiqh, and the History of Islamic Civilization) and aligned with the P5 Sustainable Lifestyle theme and Local Wisdom. The challenges include issues at the levels of: policy (weak technical guidelines and monitoring), curriculum (implicit material and limited teaching resources), teachers (limited pedagogical competence), students (low awareness and a gap between theory and practice), and schools (minimal facilities, limited budgeting, and low community awareness). Strategic solutions include the development of technical guidelines, the establishment of explicit competencies, funding mechanisms and monitoring indicators, module development, continuous teacher training, action-based learning, cross-institutional collaboration, and transformation toward eco-schools/eco-madrasahs. Abstrak Krisis lingkungan global mendorong Kementerian Agama RI pada 2025 mengintegrasikan ekoteologi ke dalam kurikulum Pendidikan Agama Islam sebagai respons atas kebutuhan pembentukan kesadaran ekologis berbasis iman di jenjang menengah. Penelitian ini bertujuan untuk menganalisis konsep ekoteologi dalam kebijakan Kemenag 2025, menelaah strategi integrasinya ke PAI, serta mengidentifikasi problematika dan solusi strategis untuk SMA/MA. Metode yang dipakai adalah studi literatur deskriptif-analitis terhadap dokumen kebijakan, artikel ilmiah, dan buku relevan. Temuan menunjukkan bahwa ekoteologi dalam kebijakan tersebut dibangun atas lima prinsip Islam, yaitu Tauhid, Khalifah dan Amanah, Mizan, larangan israf dan anjuran ihsan, serta pengakuan kedaulatan Tuhan atas alam, kebijakan juga menonjolkan konsep “zikir sosial” yang memaknai merawat lingkungan sebagai ibadah. Integrasi disarankan melalui lima ranah pembelajaran (Al-Qur’an-Hadits, Akidah, Akhlak, Fikih, dan Sejarah Peradaban Islam) dan selaras dengan tema P5 Gaya Hidup Berkelanjutan serta Kearifan Lokal. Problematika meliputi dimensi kebijakan (juknis dan monitoring lemah), kurikulum (materi implisit, bahan ajar terbatas), guru (kompetensi pedagogis terbatas), siswa (kesadaran rendah, kesenjangan teori-praktek), dan sekolah (sarpras dan anggaran minim, kesadaran masyarakat rendah). Solusi strategis mencakup penyusunan juknis, penetapan kompetensi eksplisit, mekanisme pendanaan dan indikator pemantauan, pengembangan modul, pelatihan berkelanjutan bagi guru, pembelajaran aksi, kolaborasi lintas lembaga, dan transformasi menuju eco-school/eco-madrasah.